2014
DOI: 10.1088/1367-2630/16/4/043022
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced reconstruction of weighted networks from strengths and degrees

Abstract: Network topology plays a key role in many phenomena, from the spreading of diseases to that of financial crises. Whenever the whole structure of a network is unknown, one must resort to reconstruction methods that identify the least biased ensemble of networks consistent with the partial information available. A challenging case, frequently encountered due to privacy issues in the analysis of interbank flows and Big Data, is when there is only local (node-specific) aggregate information available. For binary n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
216
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(226 citation statements)
references
References 29 publications
9
216
1
Order By: Relevance
“…The performances of this newly proposed approach are shown to outperform those obtained with standard maximum entropy approaches (Saracco et al, 2015), i.e. the bipartite extensions of the models proposed by Mastrandrea et al (2014) for unipartite networks.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The performances of this newly proposed approach are shown to outperform those obtained with standard maximum entropy approaches (Saracco et al, 2015), i.e. the bipartite extensions of the models proposed by Mastrandrea et al (2014) for unipartite networks.…”
Section: Introductionmentioning
confidence: 92%
“…Since other specifications of maximum entropy are quite popular in the literature of network reconstruction, only for comparison purposes we take into considerations two other ensembles, mainly inspired by the paper by Mastrandrea et al (2014) and Saracco et al (2015). Each of them is characterized by different constraints imposed on the maximization of the Shannon's entropy.…”
Section: The Maximum Entropy Principlementioning
confidence: 99%
See 1 more Smart Citation
“…Outside of behavioural ecology, there is a growing suite of random-graph algorithms (Watts & Strogatz, 1998;Serrano et al, 2006;Leskovec et al, 2010;Ansmann & Lehnertz, 2011;Prettejohn et al, 2011) which emphasise core properties such as the degree-sequence, strength-sequence, network size and density; they have shown that unless such properties are held constant across random-graphs, then any conclusions about network properties will just reect variation in the degreesequence, strength-sequence, network-size, etc. There is a near consensus about the need to condition on the degree-sequence for binary-networks, but the matter is more controversial for weighted-networks, and one's conclusions are sensitive to such conditioning (Garlaschelli & Loredo, 2009;Mastrandrea et al, 2014). This paper follows in the spirit of Garlaschelli & Loredo (2008), to calculate metric expectations based on null-models that assume only basic individual-level properties, and to do so by generating an ensemble of random networks based on the Exponential Random Graph formulation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Garlaschelli & Loredo (2009) discovered that some weighted measures "inherit" trivially from topological features and called for "a systematic redenition of weighted network properties", while Mastrandrea et al (2014) noted that "the strength sequence is in general uninformative about the higher-order properties of the network". The implications for behavioural ecologists are that: 1) many weighted-network metrics may not depend on weights per se and actually depend on the underlying binary, topological patterns; and 2) that many metrics of higher-order structure are not signicantly dierent from (and often highly corrected with) the values one would expect from networks with only individual-level constraints (degree and/or strength).…”
Section: Introductionmentioning
confidence: 99%